ENHANCING STUDENTS' CREATIVITY: IMPLEMENTING DIGITAL LITERACY THROUGH A TELEGRAM CHATBOT FOR CREATIVE PROJECTS AT YAYASAN PENDIDIKAN BINA BERSAUDARA - Rita Hartati; Meisuri, Meisuri; Siti Aisyah Ginting; Ariatna, Ariatna (JURNAL PENGABDIAN MANDIRI, 2024)
Technological advances provide great benefits in various fields, including education. This service project aims to improve students' creativity and digital literacy through the implementation of Telegram chatbot at Bina Bersaudara Education Foundation. The main objective is to address the lack of utilization of digital technology by students for school promotion and enhance their creativity. The method used involved selecting 20 students based on their technological potential, providing intensive training on chatbot development and usage, as well as involving them in creative content creation for YouTube. The results showed Chatbot support Students' Creativity for Creative Projects. The findings show that 25% of students rated the chatbot support for their creative projects as excellent. A majority of 60% found the support to be very good, indicating that the chatbot met their needs effectively. Chatbot support Students' digital literacy. The findings indicate that 15% of students rated the chatbot support for their digital literacy as excellent. A significant majority of 70% found the support to be very good, suggesting that the chatbot was effective and met their needs well. In summary, the findings reflect a positive overall reception of chatbot support for creative projects and for digital literacy with significant room for minor improvements to achieve a higher level of excellence